Neutron imaging data processing using the Mantid framework. (September 2016) - Pouzols, Federico M.; Draper, Nicholas; Nagella, Sri; Yang, Erica; Sajid, Ahmed; Ross, Derek; Ritchie, Brian; Hill, John; Burca, Genoveva; Minniti, Triestino; Moreton-Smith, Christopher; Kockelmann, Winfried
Abstract: Several imaging instruments are currently being constructed at neutron sources around the world. The Mantid software project provides an extensible framework that supports high-performance computing for data manipulation, analysis and visualisation of scientific data. At ISIS, IMAT (Imaging and Materials Science & Engineering) will offer unique time-of-flight neutron imaging techniques which impose several software requirements to control the data reduction and analysis. Here we outline the extensions currently being added to Mantid to provide specific support for neutron imaging requirements.